Management of peri-implant tissues with screwed provisionals in bilateral agenesis: Case report - Guerra, Raquel (2021)
One of the treatment alternatives for cases of lateral incisors agenesis in the upper zone is through rehabilitation with dental implants. It is important to make an adequate diagnosis and a treatment plan, respecting biological times for bone regeneration and tissue management, so that the final result complies with the aesthetics that the case involves. The objetive of the present work is to report a clinical case of 24 year old male patient with superior bilateral agenesis of the lateral incisors, previously receiving orthodontic treatment for 6 years, the next part of the treatment involved horizontal bone regeneration of the affected areas with autologous chin grafting, the planning of implant placement and the management of periimplant tissues.